2018
DOI: 10.1111/cid.12703
|View full text |Cite
|
Sign up to set email alerts
|

The potential clinical relevance of anatomical structures and variations of the maxillary sinus for planned sinus floor elevation procedures: A retrospective cone beam computed tomography study

Abstract: Background Complications arising from sinus floor elevation (SFE) with lateral approach surgery can be avoided by means of maxillary sinus examination in the preoperative period. Purpose To investigate anatomical variations in the maxillary sinus by making use of cone beam computed tomography (CBCT) in terms of SFE with a lateral approach. Materials and Methods Two hundred twenty eight maxillary sinuses in 114 patients were included. Parameters such as the position and diameter of the posterior superior alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 37 publications
3
15
1
Order By: Relevance
“…Irinakis et al 8 examining pre-operative CBCT images, observed the presence of interfering septa in 48.1% of the sinuses. Şimşek Kaya et al 21 showed evidence of the presence of sinus septa in 42.1% of the 114 patients. Lang, Schulze 9 found a frequency of 32% in 106 sinuses analyzed.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Irinakis et al 8 examining pre-operative CBCT images, observed the presence of interfering septa in 48.1% of the sinuses. Şimşek Kaya et al 21 showed evidence of the presence of sinus septa in 42.1% of the 114 patients. Lang, Schulze 9 found a frequency of 32% in 106 sinuses analyzed.…”
Section: Discussionmentioning
confidence: 96%
“…It is, however, important to point out that some authors determined a minimum size of sinus septum. Şimşek Kaya et al 21 adopted septa of at least 3 mm for inclusion in their study. Other authors adopted 2.5 mm as an inclusion criterion 9,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron is incorporated into ameloblasts and then into the outer layer of enamel which results in a zone of high iron content (17). It has been shown that rats suffer several abnormalities such as, significant loss of enamel pigmentation, aplasia and enamel hypoplasia due to iron deficiency (16).…”
Section: Discussionmentioning
confidence: 99%
“…This natural process varies on an individual basis however oftentimes results in volume and density loss and inadequate bone height, which limits the placement of implants of normal length. For this reason, several maxillary sinus lifting methods have been developed to increase the bone height, such as lateral window and transcrestal osteotome techniques (1).…”
Section: Introductionmentioning
confidence: 99%